Therapeutic l-asparaginase: upstream, downstream and beyond - Lopes, André Moreni; Oliveira-Nascimento, Laura de; Ribeiro, Artur; Tairum, Carlos Abrunhosa [UNESP]; Breyer, Carlos Alexandre [UNESP]; Oliveira, Marcos Antonio de [UNESP]; Monteiro, Gisele; Souza-Motta, Cristina Maria de; Magalhães, Pérola de Oliveira; Avendaño, Jorge Gonzalo Farías; Cavaco-Paulo, Artur Manuel; Mazzola, Priscila Gava; et al. (Taylor & Francis, 2017)
l-asparaginase (l-asparagine amino hydrolase, E.C.3.5.1.1) is an enzyme clinically accepted as an antitumor agent to treat acute lymphoblastic leukemia and lymphosarcoma. It catalyzes l-asparagine (Asn) hydrolysis to l-aspartate and ammonia, and Asn effective depletion results in cytotoxicity to leukemic cells. Microbial l-asparaginase (ASNase) production has attracted considerable attention owing to its cost effectiveness and eco-friendliness. The focus of this review is to provide a thorough review on microbial ASNase production, with special emphasis to microbial producers, conditions of enzyme production, protein engineering, downstream processes, biochemical characteristics, enzyme stability, bioavailability, toxicity and allergy potential. Some issues are also highlighted that will have to be addressed to achieve better therapeutic results and less side effects of ASNase use in cancer treatment: (a) search for new sources of this enzyme to increase its availability as a drug; (b) production of new ASNases with improved pharmacodynamics, pharmacokinetics and toxicological profiles, and (c) improvement of ASNase production by recombinant microorganisms. In this regard, rational protein engineering, directed mutagenesis, metabolic flux analysis and optimization of purification protocols are expected to play a paramount role in the near future.
Keywords: Acute lymphoblastic leukemia; antineoplastic activity; biopharmaceutical; l-asparaginase; microbial l-asparaginase production